ANALISIS TOLL CHARGE USING ATP/WTP FOR KRAKSAAN – BANYUWANGI TOLL ROAD - Hary Putra, Achmad Prayoga; Kusumaningrum, Rahayu; Silmy Adani, Sakila Herfiana (Jurnal Mahasiswa Jurusan Teknik Sipil, 2017)
East Java is the second most populous province in Indonesia, based on census data given by Central Bureau of Statistics. The population density in East Java also in line with its density in the sector of transportation. The route has low safety level since there is PLTU Paiton that could affect the road user when there is work accident. To handle density and safety problem, a construction of Kraksaan-Banyuwangi toll was planned to support the Trans-Java Toll. In this construction plan, an investigation of ideal tariff based on user perception using ATP and WTP analysis was required. Data collection was done in Besuki sub-district with 2 locations of survey. The survey was conducted with the method of interview and closed questionnaire for 422 respondents. According to the graphic of relationship between those two methods, the result of respondents characteristic and ideal tariff of Kraksaan-Banyuwangi toll is acquired as follows: Group 1 Rp.625,00/Km, Group 2 Rp. 937.50/Km, Group 3 Rp. 1.250,00/Km, Group 4 Rp.1.562,50/Km, and Group 5 Rp. 1.875,00/Km. The ideal tariff obtained is deemed as low compared to toll tariff in the district of Surabaya, Gempol, Sidoarto and Mojokerto. The difference is regarded as normal considering the growth value of Kraksaan-Banyuwangi region that is still below the aforementioned districts– according to Central Bureau of Statistics (BPS). The low ideal tariff is also influenced by the perception of respondents towards the transportation density of the route that is still considered as normal. Since most of the respondents have never used any toll road before, they also assumed that alternative road / toll is still unimportant. Keywords: Tariff, ATP, WTP